2013
DOI: 10.1111/apt.12451
|View full text |Cite
|
Sign up to set email alerts
|

The effects of probiotics on barrier function and mucosal pouch microbiota during maintenance treatment for severe pouchitis in patients with ulcerative colitis

Abstract: SUMMARY Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 55 publications
0
41
0
2
Order By: Relevance
“…Gionchetti et al also showed that VSL#3 for one year beginning within one week of ileostomy closure decreased onset of pouchitis from 40% in the placebo group to 10% in the treated group [83]. Unfortunately, other agents have not been studied extensively, so it is unclear if these results are unique to VSL#3, although a different probiotic mixture, Ecologic 825, appeared to improve mucosal barrier function as measured by ex vivo bacterial translocation [84]. Lactobacillus GG had no efficacy in acute pouchitis [85], although VSL#3 showed some benefit in an open label study [86].…”
Section: Probioticsmentioning
confidence: 99%
“…Gionchetti et al also showed that VSL#3 for one year beginning within one week of ileostomy closure decreased onset of pouchitis from 40% in the placebo group to 10% in the treated group [83]. Unfortunately, other agents have not been studied extensively, so it is unclear if these results are unique to VSL#3, although a different probiotic mixture, Ecologic 825, appeared to improve mucosal barrier function as measured by ex vivo bacterial translocation [84]. Lactobacillus GG had no efficacy in acute pouchitis [85], although VSL#3 showed some benefit in an open label study [86].…”
Section: Probioticsmentioning
confidence: 99%
“…In this model, the administration of a probiotic mixture prevented not only the decrease in TJ proteins expression, but also the increase of epithelial apoptotic ratio induced by acute colitis [212]. Furthermore, in patients with severe pouchitis, probiotics were able to restore the mucosal barrier, as they decreased E. coli K12 passage through the intestinal epithelium in Ussing chambers [213].…”
Section: Intestinal Microbiotamentioning
confidence: 80%
“…Induce the production of antiinflammatory cytokines. A recent publication from our group using this specific mixture of probiotics has shown restored mucosal barrier properties in patients with chronic pouchitis 272 . One drawback of working with a mixture of probiotics is that it is harder and time consuming to study the specific effects of each strain.…”
Section: Probioticsmentioning
confidence: 95%